Kidfluencers in India: Commodification, Consumption, and Perpetuation of Dominant Culture - Devina Sarwatay (Social Media + Society)
Despite online risks and child labor concerns, Indian kidfluencers appear to thrive as they amass followers and engage in brand collaborations, thus significantly contributing to India’s influencer industry. I studied and analyzed selected kidfluencers’ profiles and their most popular videos and found that their parents manage their accounts and direct their content. This content often reflects dominant Indian culture using language, the portrayal of religious identities, and the enactment of family values. This strategy increases their follower counts but also exposes them to online risks and reinforces cultural stereotypes. Kidfluencers face exploitation as they scale their presence—that is, get more followers on a specific platform and get multiple accounts across platforms—on social media, especially in India where regulation is lacking. Abuse, bullying, and mental health issues are prevalent, necessitating urgent policy and advocacy efforts.